Evaluation of strength properties of parallel splint lumber(PSL) and its comparison with laminated veneer lumber(LVL), rubber wood and teak - Shukla S R; Rao R V; Sharma S N (Holz Als Roh-und Werkstoff, 1999)
Strength properties of parallel splint lumber(PSL) made of rubber wood(Hevea brasiliensis) and an exterior type of adhesive were evaluated in air-dry condition. Block shear tests were also carried out in wet and dry condition. Comparisons of these strength values were made with those of laminated veneer(LVL), solid rubber wood and standard teak [Tectona grandis]. The results show that PSL has slightly lower values of strength properties compared with teak and solid rubber wood, and quite inferior ones to those of LVL. On the basis of the data obtained in the present study, PSL made from rubber wood can be utilised as a structural material for different purposes like door and window frames, rings and trusses.
Source Year: 2000
Keywords: Laminated veneer lumber; Parallel splint lumber; Rubber wood